Redescription of Lepismatophila cruszi Kundu and Haldar, 1984 (Apicomplexa : Sporozoea) from Chondracis rosea (Order: Orthoptera) - N. Mohilal, Indira Yumnam; Shah, M. Manjur (Recent Research in Science and Technology, 2020)
This study describes external characteristics and life history of a species of cephaline gregarine (Apicomplexa: Sporozoea) of the genus Lepismatophila [1], from Chondracis rosea (Order: Orthoptera)of Manipur, India. Diagnosis characteristic of the species the epimerite a simple symmetrical knob, Protomerite present throughout trophozoite stage, Solitary nature of Sporadins, Cyst without ducts dehiscence by simple rupture and Spores in uncoiling chains, ellipsoidal, boat shaped, without any filamentous process are discussed. And the morphological details of the different stages supported with photomicrographs are also provided.